Coaching Teachers in Detection and Intervention Related to Bullying, Mid-Atlantic Region, 2016-2018 - Bradshaw, Catherine P. (Catherine Pilcher) ([Verlag nicht ermittelbar], 2020)
This study focuses on bullying prevention in classroom context. An approach was used to address bullying in the classroom through an adapted version of the Classroom Check-up coaching model, which is combined with a mixed-reality simulator called TeachLivE to build teacher skills in preventing, detecting, and responding to bullying.